E-Module Design Workshop as Professional Development Program for Pre-School Teachers - Nurbatra, Laela Hikmah; Masyhud (Universitas Pendidikan Ganesha, 2023)
Early childhood education is a form of education that places the children at the centre of the learning process and is adapted to the child's developmental stage. To conduct an engaging and meaningful process in Early Childhood Education (PAUD), teachers are expected to improve their capacities in order to catch up with the technological development. The proposed community empowerment program would involve KB Taman Harapan which is located at Jl Raya Sumbersekar No 108 RT 01 RW 03 Krajan, Sumbersekar, Malang. Based on what was observed and what was stated in the interview with the principal, KB Taman Harapan is struggling with challenges. In the first place, they are having trouble dealing with the lack of professional development programs for the teachers. Second, the principal indicated that they are also dealing with some financial issues. Lastly, the principal also mentioned that they were having difficulty generating interesting resources for online instruction. The main agendas would be organized to solve the issues, namely providing training for e-module development program for teachers and providing a tryout session for the results of the e-module. In the process, there would be 4 stages of action: (1) Planning, (2) implementation, (3) Evaluation.